Implementasi Metode Pembiasaan : Upaya penanaman Nilai-Nilai Islami Siswa SDN 08 Rejang Lebong - Vebri Angdreani; Idi Warsah; Asri Karolina (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Implementation of habituation method: The effort to instill Islamic values into the students of SDN 8 Rejang LebongEvery child’s positive behavior is not necessarily attributed to their inborn character, but it is passed down through a process of habituation. Habituation as a learning method is assumed to be a proper way to embed Islamic values into students so that it develops into a culture at school. Anchored in this assumption, this study sought to find out a depiction of the habituation method implementation in an effort to instill Islamic values of SDN 08 Rejang Lebong students. The method used to obtain this depiction was a qualitative method by conducting interviews and observations to the study objects until the accurate data were gained and then analyzed using Miles and Huberman’s stages of data analysis. This study revealed that the habituation learning method was seen to be effective in instilling Islamic values in SDN 08 Rejang Lebong, and to date those values can be well-maintained